Some Kaleckian remarks on modern monetary theory in light of a paper by Drumetz/Pfister - Malcolm C. Sawyer (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
This paper provides remarks on modern monetary theory (MMT) from a Kaleckian perspective in response to a paper by Drumetz/Pfister. The distinction between initial financing and final financing is drawn up to argue for clear separation of how expenditure is financed and funded, and pointing to the confusions that have arisen. Some issues of crowding in and crowding out are raised. Some aspects of inflation and hyper-inflation are then discussed. The conditions for the establishment of full employment are elaborated. While MMT has focused on financing of government expenditure and aggregate demand, Kaleckians and post-Keynesians have analyses and theories on the operations of the whole economy which differ sharply from those of mainstream economists.
Keywords: E11; E12; E40; E62; 330; modern monetary theory; Kalecki; money; budget deficit; inflation